Synthesis of coumarin-3-carboxylic acids in waste curd water: A green approach - Sonawane, Nitin Bhaidas; Rajput, Jamatsing Dabarsing; Patil, Dilip Ramsing (European Journal of Chemistry, 2023)
An efficient and green protocol has been developed for the synthesis of derivatives of coumarin-3-carboxylic acid using waste curd water as a catalytic solvent. Curd water successfully catalyzes the reaction of 2-hydroxybenzaldehydes with dimethyl malonate under ultrasonic irradiation (40 °C) to construct different scaffolds of coumarin-3-carboxylic acid, with good to outstanding yields. The use of biodegradable solvents, sustainability, low reaction duration, mild reaction conditions without metals and Lewis acids, excellent yields, and compatibility with a wide range of electronically diverse substrates are all advantages of this synthesis process. Acidic curd water, which acts as a biological catalyst as well as a solvent for the reaction under ultrasonic irradiation, may be a better green alternative to some standard methods for synthesizing coumarin-3-carboxylic acids.